(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge and practice of breastfeeding and to analyze associated factors among postpartum women at Hai Phong University Hospital in 2025. Methods: A cross-sectional descriptive study was conducted among 250 postpartum women at the Department of Obstetrics and Gynecology, Hai Phong University Hospital, from January to June 2025. Data were collected through face-to-face interviews using a structured questionnaire developed based on WHO, UNICEF, and the Vietnam Ministry of Health recommendations. Knowledge and breastfeeding practice were assessed using a scoring system, with a cut-off point of ≥75% considered adequate. Data were analyzed using SPSS version 20.0. Results: The proportion of women with adequate breastfeeding knowledge was 82%, and knowledge of the benefits of breast milk for infants was high (91.6–98.4%). The rate of adequate breastfeeding practice was 76%. However, only 59.2% of mothers initiated breastfeeding within the first hour after delivery. Ethnicity (Kinh) and parity were significantly associated with breastfeeding knowledge. Breastfeeding practice was significantly higher among multiparous women (p < 0.05). Conclusion: The knowledge and practice of breastfeeding among postpartum women at Hai Phong University Hospital were relatively good; however, a gap between knowledge and practice still exists. Strengthening counseling and practical support for breastfeeding after delivery is necessary